Ferromagnetic, Folded Electrode Composite as a Soft Interface to the Skin for Long‐Term Electrophysiological Recording. (9th September 2016) - Jang, Kyung‐In; Jung, Han Na; Lee, Jung Woo; Xu, Sheng; Liu, Yu Hao; Ma, Yinji; Jeong, Jae‐Woong; Song, Young Min; Kim, Jeonghyun; Kim, Bong Hoon; Banks, Anthony; Kwak, Jean Won; et al.
Abstract : A class of ferromagnetic, folded, soft composite material for skin‐interfaced electrodes with releasable interfaces to stretchable, wireless electronic measurement systems is introduced. These electrodes establish intimate, adhesive contacts to the skin, in dimensionally stable formats compatible with multiple days of continuous operation, with several key advantages over conventional hydrogel‐based alternatives. The reported studies focus on aspects ranging from ferromagnetic and mechanical behavior of the materials systems, to electrical properties associated with their skin interface, to system‐level integration for advanced electrophysiological monitoring applications. The work combines experimental measurement and theoretical modeling to establish the key design considerations. These concepts have potential uses across a diverse set of skin‐integrated electronic technologies. Abstract : A ferromagnetic, folded, soft‐electrode composite material with long‐term usage and system‐level integration in electrophysiological monitoring is introduced. Systematic investigations including the ferromagnetism behaviors, mechanical properties, electrical interfaces to the skin, and their materials aspects are carried out. The electrodes provide advantages in non‐irritating contacts to the skin, dimensionally stable geometries, and robust bonding to the skin and the measurement platforms.